Fenvalerate Toxicity in a Germen Shephard Dog - Parmar, J.J.; Parikh, P.V.; Gondaliya, R.B.; Chevelikar , P.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Synthetic pyrethroids account for more than 30% of insecticides used worldwide in household, agricultural and veterinary applications. Fenvalerate is synthetic pyrethroid used in agriculture, homes, gardens, and also in livestock alone or in combination with other insecticides (Ramana Murthy et al., 2015). Fenvalerate is used since 1980 in India, yet its toxicity has not been reported so far. This case report describes acute toxicity of fenvalerate in a dog.
Keywords: Fenvalerate; Toxicity; Dog